The relationship between vitamin D and insulin resistance before delivery in advanced maternal age - Beibei Dong; Mengmeng Zhi; Manman Han; Hao Lin; Hong Yu; Ling Li (BMC, 2019)
Abstract Background With the widely implementation of universal two-child policy, the number of pregnant women in advanced maternal age (AMA) will increase gradually. We aimed to assess the association of vitamin D levels and insulin resistance (IR) during the late pregnancy in AMA. Methods A total of 80 pregnant women were consecutively enrolled in the cross-sectional study before delivery from the August 2016 to June 2017 at the department of gynecology and obstetrics in the hospital of ZhongDa, affiliated to Southeast University. At delivery, serum 25(OH) D and metabolism parameters including glucose and lipid levels were measured. IR was calculated by the method of homeostasis model assessment 2(HOMA2). Results Pregnant women in AMA with vitamin D deficiency have higher fasting insulin (14.70(8.76-34.65) and 10.89(7.15-16.12), respectively, P = 0.031) and HOMA-IR indices (1.78(1.07-4.14) and 1.30(0.83-1.89), respectively, P = 0.024) than those with vitamin D non-deficiency. Serum 25(OH) D levels were inversely associated with HOMA-IR indices (r = − 0.25, P = 0.025). In multivariable analysis for adjusting confounder factors, vitamin D non-deficiency was also negatively correlated with HOMA-IR compared to vitamin D deficiency (β = − 1.289, P = 0.026). Conclusions Taken together, our findings suggest that serum 25(OH) D levels were inversely associated with HOMA-IR in AMA. Furthermore, pregnant women in AMA with vitamin D deficiency might have higher HOMA-IR levels than those with vitamin D non-deficiency. Trial registration Chinese Clinical Trial Registry (No. ChiCTR-RRC-16008714). retrospectively registered.